Transforming Maine’s Economy: Innovation and Entrepreneurship Policy - Renault, Catherine (Maine Policy Review, 2014)
Innovation and entrepreneurship are major drivers of economic growth. Support for them is a primary role of state government in order to increase the well being of its citizens through the provision of well-paying jobs that cannot be easily exported. Today, the state’s role is described as “enhancing the innovation ecosystem,” with the goal of increased productivity, innovation and competitiveness. Policies to build the ecosystem include: (1) building and supporting a state’s research and development capacity; (2) encouraging a state’s entrepreneurial community, (3) increasing the productivity of a state’s economy though the commercialization of new products, services, processes, business models and marketing strategies and (4) supporting sectors and/or clusters. Each of these is part of an overall policy environment that will support innovation and entrepreneurship.
Keywords: innovation; entrepreneurship; state government; innovation ecosystem; Maine